Glass composition, glass paste, sealing package, and coated substrate

A lead-free glass composition with balanced SiO2, B2O3, Li2O, Na2O, K2O, BaO, and Al2O3 addresses environmental concerns and ensures stability and compatibility with ceramic substrates in pressure sensors, providing effective adhesion and resistance at low sintering temperatures.

JP2025013137APending Publication Date: 2025-01-24AGC INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024037220
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-12
Filing Date
2024-03-11
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing glass materials used in pressure sensors for automobiles, medical care, and construction contain lead, which is environmentally harmful, and require lead-free alternatives that maintain stability, heat resistance, and acid/alkaline resistance while ensuring compatibility with ceramic substrates like alumina, particularly at sintering temperatures below 850°C.

Method used

A lead-free glass composition comprising specific ranges of SiO2, B2O3, Li2O, Na2O, K2O, BaO, and Al2O3, balanced to provide excellent adhesion, acid resistance, alkaline resistance, and thermal expansion matching ceramic substrates, with a glass transition point of 510 to 570°C and thermal expansion coefficient of 62×10-7 to 78×10-7/°C.

Benefits of technology

The glass composition achieves stable sintering below 850°C, maintains acid and alkaline resistance, and matches thermal expansion with ceramic substrates, ensuring reliable adhesion and reducing environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025013137000002
    Figure 2025013137000002
  • Figure 2025013137000003
    Figure 2025013137000003
  • Figure 2025013137000001
    Figure 2025013137000001
Patent Text Reader

Abstract

To provide a glass composition that exhibits sufficient coating and sealing performance at sintering temperatures of 850°C or less, without substantial lead content, and yields a glass with superior acid and alkali resistance, with the thermal expansion coefficient controlled within a specific range.SOLUTION: A glass composition is substantially free of Pb and contains, in mass% on an oxide basis, SiO2 of 66-75%, B2O3 of 5-11.5%, Li2O of 0.5-10%, Na2O of 0-10%, K2O of 0-10%, BaO of 3.1-10%, and Al2O3 of 0-4%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a glass composition, a glass paste, a sealed package, and a substrate with a covering layer. [Background technology]

[0002] Ceramic substrates such as alumina are used as elements of pressure sensors that are used in various fields such as automobiles, medicine, and construction. It is known that glass is used as a material for covering the circuits formed on the elements and for bonding or sealing components together.

[0003] Conventionally, such glass for coating or bonding / sealing has been blended with lead in order to improve the stability and productivity of the glass. For example, Patent Document 1 describes a sealing glass material containing 70 to 80 mass % of PbO on an oxide basis. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2000-505414 Summary of the Invention [Problem to be solved by the invention]

[0005] However, from the viewpoint of reducing the environmental load, there has been a demand in recent years for lead-free glass materials.

[0006] On the other hand, glass materials for coating or bonding / sealing are required to be able to ensure coating and sealing properties even at glass sintering temperatures that take into account the heat resistance of the elements to which they are applied, specifically at temperatures of 850°C or lower. Furthermore, in order to ensure reliability in the environment in which the element is used, the resulting glass is required to have sufficient resistance to acids and alkalis. Furthermore, assuming that the element will be used under severe temperature cycling conditions, the thermal expansion of the element's substrate and that of the glass must be close to each other. If the thermal expansion of the two differs too much, the glass may crack, compromising the reliability of the element.

[0007] In view of the above, an object of the present invention is to provide a glass composition which is substantially free of lead, has sufficient covering and sealing properties even at a sintering temperature of 850° C. or less, provides glass with excellent acid resistance and alkali resistance, and has a thermal expansion coefficient within a specific range. Another object of the present invention is to provide a glass paste containing the glass composition, a sealing package having a sealing layer containing the glass composition, and a substrate with a coating layer having a coating layer containing the glass composition. [Means for solving the problem]

[0008] The present inventors have found that the above problems can be solved by using a glass composition having a glass composition within a specific range, and have completed the present invention. The present invention relates to a glass composition having the following composition. Contains virtually no Pb In terms of mass% based on oxides, SiO 2 66~75% B 2 O 3 5 to 11.5%, Li 2 0.5 to 10% O Na 2 O 0 to 10%, K 2 O 0 to 10%, BaO 3.1-10%, Al 2 O 3 0 to 4%, A glass composition comprising: Effect of the Invention

[0009] According to the glass composition of the present invention, even if it is substantially free of lead, it is possible to obtain glass that has sufficient covering properties and sealing properties at a sintering temperature of 850° C. or less, has excellent acid resistance and alkali resistance, and has a thermal expansion coefficient within a specific range. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a cross-sectional view showing one embodiment of a sealed package. [Diagram 2] FIG. 2 is a cross-sectional view showing one embodiment of a substrate with a cover layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention will be described. Note that the present invention is not limited to the embodiment described below.

[0012] In this specification, unless otherwise specified, the "%" for the content of each component of the glass composition is expressed on an oxide basis, that is, as mass% converted into oxide. In this specification, the use of "to" to indicate a numerical range is intended to include both the upper and lower limits.

[0013] <Glass composition> The glass composition of the present embodiment is substantially free of Pb (lead) and contains, in mass % on an oxide basis, SiO 2 66-75%, B 2 O 3 5 to 11.5%, Li 2 O 0.5-10%, Na 2 O 0-10%, K 2 O 0-10%, BaO 3.1-10%, Al 2 O 3 Contains 0-4%.

[0014] Conventional glass compositions contain lead (PbO) to suppress phenomena such as crystallization, phase separation, and non-melting, and to produce glass stably. On the other hand, the glass composition of the present embodiment does not substantially contain Pb (lead) from the viewpoint of reducing the environmental load. Here, "substantially not containing" means that it does not contain anything other than unavoidable impurities, that is, it means that it is not intentionally added. Therefore, the glass composition of the present embodiment may contain a trace amount of Pb as an unavoidable impurity. The content of PbO in the glass composition of the present embodiment is preferably 1000 mass ppm or less, more preferably 500 mass ppm or less. According to the glass composition of the present embodiment, since it has a specific glass composition, glass can be stably produced without containing lead.

[0015] SiO 2 is a component that forms the glass skeleton. SiO 2 Although SiO promotes the crystallization of glass, if the amount is too large, there is a concern that phase separation or non-melting may occur, and there is also a concern that the thermal expansion coefficient of the glass may become too high due to crystal growth. 2 The content is 75% or less, preferably 74% or less, and more preferably 72% or less. In addition, SiO 2 The smaller the SiO content in the glass composition, the better the sinterability of the glass. However, there is a concern that the acid resistance and alkali resistance of the glass may decrease, and the reactivity with the electrodes may increase. 2 The content is at least 66%, preferably at least 67%.

[0016] B 2 O 3 is a component that forms a glass skeleton and expands the range of vitrification. 2 It has a weaker skeleton than , and is a component that lowers the softening point of glass. B 2 O 3 The more B in the glass composition, the more the sinterability of the glass improves, but there is a concern that the acid resistance and alkali resistance of the glass may decrease and the reactivity with the electrodes may increase. 2 O 3 The content is not more than 11.5%, preferably not more than 10.0%. Also, B 2 O 3 The smaller the content of B in the glass composition, the more the crystallization of the glass is promoted. However, if the content is too small, there is a concern that phase separation or non-melting may occur, and there is also a concern that the thermal expansion coefficient of the glass may become too high due to crystal growth. From this viewpoint, the B content in the glass composition is 2 O 3 The content is 5% or more, preferably 6% or more, and more preferably 8% or more.

[0017] Li 2 O is a component that cuts the glass skeleton and lowers the softening point of the glass. Moreover, among alkali metals, alkali metals have the best adhesion to alumina, and therefore, when the substrate to which the glass composition is applied is an alumina substrate, adhesion can be particularly improved. Li 2 The more O, the better the sinterability of the glass, but there is a concern that the acid resistance and alkali resistance of the glass may decrease and the reactivity with the electrodes may increase. In addition, if the amount is too large, there is a concern that phase separation or non-melting may occur, and the thermal expansion coefficient of the glass may become too high due to crystal growth. From this viewpoint, the amount of Li in the glass composition is 2 The O content is 10% or less, preferably 5% or less, and more preferably 2% or less. In addition, in order to improve adhesion to alumina, the Li 2 The O content is 0.5% or more, and preferably 1.0% or more.

[0018] Na 2 O and K 2 O is a component that cuts the glass skeleton and lowers the softening point of the glass. Furthermore, since the glass composition has excellent adhesion to alumina, when the substrate to which the glass composition is applied is an alumina substrate, the adhesion can be particularly improved. Na 2 O and K 2The more O, the better the sinterability of the glass, but there is a concern that the acid resistance and alkali resistance of the glass may decrease, and the reactivity with the electrodes may increase. In addition, if the amount is too large, there is a concern that phase separation or non-melting may occur, and the thermal expansion coefficient of the glass may become too high due to crystal growth. From this viewpoint, Na in the glass composition is 2 The O content is 10% or less, preferably 8% or less. 2 The O content is 10% or less, preferably 8% or less, and more preferably 6.5% or less. In addition, in order to improve adhesion to alumina, Na in the glass composition 2 The O content is preferably 3% or more, more preferably 5% or more, and K 2 The O content is preferably 3% or more.

[0019] BaO is a component that stabilizes glass and relatively lowers the softening point of glass. The more BaO, the better the sinterability of the glass, but the acid resistance and alkali resistance of the glass may decrease, and the reactivity with the electrodes may increase. If the BaO content is too high, phase separation and non-melting may occur, and the thermal expansion coefficient of the glass may become too high due to crystal growth. From this viewpoint, the BaO content in the glass composition is 10% or less, preferably 8% or less, and more preferably 7% or less. From the viewpoints of adhesion to alumina, suppression of a decrease in the thermal expansion coefficient, and glass stability, the BaO content in the glass composition is 3.1% or more, preferably 3.2% or more, and more preferably 3.3% or more.

[0020] Al 2 O 3 is a component that forms the glass skeleton. Al 2 O 3 If the amount of Al is too large, there is a concern that phase separation or non-melting may occur. Therefore, the amount of Al in the glass composition is 2 O 3 The content is not more than 4%, preferably not more than 3.5%. Al 2 O 3The smaller the Al content, the better the sinterability of the glass. However, if the content is too small, there is a concern that the acid resistance and alkali resistance of the glass may decrease and the reactivity with the electrodes may become high. From this viewpoint, the Al content in the glass composition is 2 O 3 The content is preferably 1.5% or more, more preferably 2% or more.

[0021] Of the above components, BaO, Li 2 O, Na 2 OK 2 O, Al 2 O 3 , and SiO 2 The contribution ratios to glass formation are different. Therefore, in order to obtain glass that is excellent in sinterability, acid resistance, alkali resistance, similarity in thermal expansion coefficient to the ceramic substrate material (preferably alumina), and productivity, which is the subject of the present invention, it is preferable that the following ratio, taking into consideration the balance of the contents of the above components, is within a specific range. That is, (4BaO+3Li 2 O+2Na 2 O+K 2 O) / (Al 2 O 3 +SiO 2 ) is preferably 0.41 to 0.70, more preferably 0.42 to 0.68, and particularly preferably 0.45 to 0.64. In this relational formula, Al, which is a component that firmly forms the glass skeleton, 2 O 3 and SiO 2 The denominator is the sum of the contents of BaO and Li, which are components that lower the softening point of glass. 2 O, Na 2 OK 2 BaO, which has O as a molecule, lowers the softening point of glass and is easy to stabilize glass, has a large contribution rate and is therefore set to the highest coefficient. If there is too much, phase separation and non-melting will occur, promoting crystallization, but Li, which has a large contribution rate and is a component that lowers the softening point of glass, 2 O is set next highest.

[0022] The glass composition according to this embodiment may contain any components other than those described above. Although CaO and SrO are components that stabilize the glass, it is preferable to contain BaO. The more CaO and SrO, the better the sinterability of the glass, but there is a concern that the acid resistance and alkali resistance of the glass will decrease and the reactivity with the electrode will increase. If the amount is too much, there is a concern that phase separation and non-melting will occur, and the thermal expansion coefficient of the glass will become too high due to crystal growth. From this viewpoint, the CaO content and SrO content in the glass composition are each preferably 10% or less, more preferably 5% or less, and particularly preferably substantially free of CaO and SrO.

[0023] ZnO is a component that lowers the softening point of glass. The more ZnO is contained, the more the sinterability of the glass improves, but there is a concern that the acid resistance and alkali resistance of the glass may decrease, and the reactivity with the electrodes may increase. From this viewpoint, the ZnO content in the glass composition is preferably 10% or less, more preferably 0.5% or less, and particularly preferably substantially free of ZnO.

[0024] Although MgO may be contained, if the amount is too large, crystals are likely to precipitate. Therefore, the MgO content in the glass composition is preferably 10% or less, more preferably 0.5% or less, and particularly preferably substantially free of MgO.

[0025] In addition, the glass composition of this embodiment contains Y 2 O 3 , La 2 O 3 , Ta 2 O 5 , SnO 2 , TiO 2 , Nb 2 O 5 , P 2 O 5 , CEO 2 , V 2 O 5 The total amount of these may be preferably 10% or less, more preferably 1% or less.

[0026] The glass composition of the present embodiment may further contain, for example, Cs 2 O, Rb 2 The total content of O etc. may be preferably 5% or less, more preferably 1% or less.

[0027] Bi 2 O 3 is a component that lowers the softening point, so the glass composition of this embodiment contains Bi 2 O 3 However, it is particularly preferable that the composition is substantially free of these. Bi 2 O 3 The content is preferably 0.3% or less, and more preferably 0.1% or less.

[0028] The glass composition of the present embodiment preferably does not substantially contain halogens such as F and Cl. The total content of halogens is preferably 0.3% or less, and more preferably 0.1% or less.

[0029] The glass composition of this embodiment has a glass transition point (hereinafter referred to as "Tg") of preferably 510 to 570°C, more preferably 515 to 565°C, and particularly preferably 520 to 560°C. If Tg is within this range, the sinterability is good and the reactivity between the glass composition and electrodes can be suppressed, which is preferable. The Tg of the glass composition can be measured using a differential thermal analyzer.

[0030] The glass composition of this embodiment has a glass softening point (hereinafter referred to as "Ts") of preferably 670 to 750°C, more preferably 680 to 740°C, and particularly preferably 685 to 720°C. If Ts is within this range, the sinterability is good and the reactivity between the glass composition and electrodes can be suppressed, which is preferable. The Ts of the glass composition can be measured using a differential thermal analyzer.

[0031] The glass composition of the present embodiment preferably has a thermal expansion coefficient of 62×10 -7 ~78×10 -7 / °C, more preferably 64×10-7 ~76×10 -7 / °C, and especially preferably 66×10 -7 ~74×10 -7 / °C. If the thermal expansion coefficient is within this range, the thermal expansion coefficient will be similar to that of the substrate of the element to which the glass composition is applied, and warping of the substrate and occurrence of cracks in the glass can be suppressed. From the viewpoint of the ease of approximating the thermal expansion coefficients, it is preferable to use a ceramic substrate as the substrate of the element, and an alumina substrate (thermal expansion coefficient: 66×10 -7 ~74×10 -7 / °C) is particularly preferred. The thermal expansion coefficient of the glass composition can be measured by preparing a sintered body of the glass composition at a sintering temperature of 800°C and using a thermal dilatometer. The thermal expansion coefficient of the glass composition means the average thermal expansion coefficient at 50 to 350°C.

[0032] The method for producing the glass composition of the present embodiment is not particularly limited. For example, the glass composition can be produced by the method described below.

[0033] First, a raw material mixture is prepared. The raw materials are not particularly limited as long as they are raw materials used in the manufacture of ordinary oxide-based glasses, and oxides, carbonates, etc. can be used. The raw material mixture is prepared by appropriately adjusting the types and ratios of the raw materials so that the composition of the resulting glass composition falls within the above-mentioned range.

[0034] Next, the raw material mixture is heated by a known method to obtain a melt. The temperature for heating and melting (melting temperature) is preferably 1450 to 1600° C., more preferably 1500° C. or higher, and more preferably 1570° C. or lower. The time for heating and melting is preferably 30 to 90 minutes.

[0035] Thereafter, the molten material is cooled and solidified to obtain the glass composition of the present embodiment. The cooling method is not particularly limited. A roll-out machine or a press machine may be used, or a method of quenching by dropping into a cooling liquid may be used. The obtained glass composition is preferably completely amorphous, that is, has a crystallinity of 0%. However, it may contain a crystallized portion as long as it does not impair the effects of the present invention.

[0036] The glass composition of the present embodiment thus obtained may be in any form, such as a block, a plate, a thin plate (flake), or a powder.

[0037] When the glass composition of the present embodiment is used as a coating material or a sealing material, the glass composition is preferably in the form of a glass powder. In addition, when evaluating the above-mentioned properties of the glass composition, the glass powder is also preferable from the viewpoint of the performance as a coating material or a sealing material.

[0038] <Glass powder> The glass powder of the present embodiment is a glass powder made of the glass composition of the present embodiment. The glass powder made of the glass composition of the present embodiment means that the average composition of the glass powder is the same as that of the glass composition of the present embodiment. That is, the glass powder of the present embodiment may be made of a glass powder having one composition that is the same as that of the glass composition of the present embodiment, or may be a glass powder obtained by mixing a plurality of glass powders having different compositions so that the average composition is the same as that of the glass composition of the present embodiment. For convenience, the glass powder made of a plurality of glass powders having different compositions will be referred to as a "glass powder mixture" hereinafter.

[0039] The particle size of the glass powder of the present embodiment can be appropriately selected depending on the application. When the glass powder of this embodiment is used as a sealing material, the particle size of the glass powder is preferably 0.1 to 100 μm. When the glass powder of this embodiment is used as a coating material, the particle size of the glass powder is preferably 0.1 to 10 μm. In addition, if the particle size of the glass powder of this embodiment is large, it is likely to settle and separate when it is made into a paste and applied or dried, and there is also a problem that the thickness of the resulting sealing layer increases. Therefore, when the glass powder of this embodiment is made into a paste and used, the particle size of the glass powder is preferably in the range of 0.1 to 5.0 μm, more preferably 0.1 to 2.0 μm, when the application is a sealing material. Furthermore, the particle size of the glass powder is preferably in the range of 0.1 to 3.0 μm, more preferably 0.1 to 2.0 μm, when the application is a coating material.

[0040] In this specification, the term "particle size" refers to the 50% particle size (D50) on a volume basis in a cumulative particle size distribution, and more specifically, refers to the particle size when the integrated amount accounts for 50% on a volume basis in a cumulative particle size curve of a particle size distribution measured using a laser diffraction / scattering type particle size distribution measuring device.

[0041] When the glass composition is used as a sealing material, the maximum particle size (Dmax) of the glass powder is preferably smaller than the thickness of the sealing layer, specifically, 1 to 30 μm, from the viewpoint of adhesion between the sealing layer and the surface to be sealed. When the glass composition is used as a coating material, the maximum particle size (Dmax) of the glass powder is preferably approximately the same as the thickness of the coating layer, specifically, 1 to 8 μm, from the viewpoint of smoothness of the coating layer.

[0042] The glass powder is obtained, for example, by pulverizing a glass composition. Therefore, the particle size of the glass powder can be adjusted by the pulverization conditions. Examples of the pulverization method include a rotary ball mill, a vibration ball mill, a planetary mill, a jet mill, an attritor, a media stirring mill (beads mill), a jaw crusher, and a roll crusher.

[0043] In particular, when making the material into fine particles of 5.0 μm or less, it is recommended to use wet milling, which involves grinding the material in a solvent such as water or alcohol using a media or bead mill made of alumina or zirconia.

[0044] In order to adjust the particle size of the glass powder, in addition to pulverizing the glass composition, classification may be carried out using a sieve or the like as necessary.

[0045] The compositions of the glass powders having different compositions constituting the glass powder mixture are not particularly limited, and the glass powder mixture of the present embodiment can be obtained by mixing appropriate types of glass powders so that the average composition is similar to the glass composition of the present embodiment described above. The glass powder mixture may be made of two types of glass powders having different compositions, or may be made of three or more types of glass powders having different compositions. In addition, when producing a glass paste containing a glass powder mixture, glass powders may be mixed to form a glass powder mixture and then made into a paste, or multiple types of pastes containing glass powders with different compositions may be mixed.

[0046] The glass powder may contain a ceramic filler, for example, to adjust the thermal expansion coefficient and abrasion resistance of the coating layer. Examples of the ceramic filler include zirconia, mullite, silica, cordierite, titania, tin oxide, etc., and one or more of these may be contained. The content of the ceramic filler in the glass powder is preferably 30 volume % or less.

[0047] <Glass paste> When the glass powder of the present embodiment is used as a sealing material or a coating material, the glass powder may be used as it is, but from the viewpoint of improving workability, it is preferable to use the glass powder in the form of a paste. The glass paste of the present embodiment preferably contains the glass powder of the present embodiment and an organic vehicle.

[0048] As the organic vehicle, for example, a solvent in which a resin, which is a binder component, is dissolved, is used. Specifically, a resin such as methyl cellulose, ethyl cellulose, carboxymethyl cellulose, oxyethyl cellulose, benzyl cellulose, propyl cellulose, or nitrocellulose dissolved in a solvent such as terpineol, texanol, butyl carbitol acetate, or ethyl carbitol acetate can be used as the organic vehicle. Also, an acrylic resin such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, or 2-hydroxyethyl (meth)acrylate dissolved in a solvent such as methyl ethyl ketone, terpineol, texanol, butyl carbitol acetate, or ethyl carbitol acetate can be used as the organic vehicle. In this specification, (meth)acrylate means at least one of acrylate and methacrylate. In addition, a polyalkylene carbonate such as polyethylene carbonate or polypropylene carbonate dissolved in a solvent such as triethyl acetyl citrate, propylene glycol diacetate, diethyl succinate, ethyl carbitol acetate, triacetin, texanol, dimethyl adipate, ethyl benzoate, or a mixture of propylene glycol monophenyl ether and triethylene glycol dimethyl ether can be used as the organic vehicle.

[0049] The ratio of the resin and the solvent in the organic vehicle is not particularly limited, but is selected so that the viscosity of the organic vehicle can adjust the viscosity of the glass paste. Specifically, the ratio of the resin and the solvent in the organic vehicle is preferably about 3:97 to 30:70 in terms of the mass ratio of the resin:solvent.

[0050] The ratio of glass powder to organic vehicle in the glass paste is appropriately adjusted according to the desired viscosity of the glass paste. Specifically, the mass ratio of glass powder to organic vehicle is preferably about 65:35 to 90:10. In addition to the glass powder and the organic vehicle, the glass paste may contain known additives as necessary and within the limits of the present invention.

[0051] The glass paste is prepared by a known method using a rotary mixer equipped with stirring blades, a roll mill, a ball mill, or the like.

[0052] <Sealed package> A sealed package to which the glass composition of the present embodiment is applied will be described. 1, a sealed package 10 of the present embodiment includes a first substrate 11 and a second substrate 12 facing each other, and a sealing layer 15 that bonds the first substrate 11 and the second substrate 12. The sealing layer 15 includes the glass composition of the present embodiment.

[0053] The first substrate 11 is, for example, an element substrate on which an electronic element section 13 is mainly provided. The second substrate 12 is, for example, a sealing substrate mainly used for sealing. The first substrate 11 is provided with the electronic element section 13. The first substrate 11 and the second substrate 12 are disposed to face each other, and are bonded therebetween by a sealing layer 15 disposed in a frame shape.

[0054] The first substrate 11 and the second substrate 12 are made of a material having a thermal expansion coefficient of 60×10 -7 ~90×10 -7 An alumina substrate having a temperature of about 1000° C. / ° C. is preferably used. An alumina substrate is preferred from the viewpoint of particularly good adhesion to the sealing layer containing the glass composition of the present embodiment. Here, alumina refers to a ceramic material containing alumina as a main component, and also includes those containing a glass-based sintering aid, a sub-crystal layer such as spinel, a black pigment, etc.

[0055] The electronic element section 13 has elements according to the application of the sealed package, such as a metal resistance element, a ceramic resistance element, and a piezo resistance element.

[0056] A method for manufacturing the sealed package of this embodiment will be described. The glass paste of the present embodiment is used as the sealing material. The glass paste is applied to the second substrate 12 in a frame shape, and then dried to form a coating layer. Examples of application methods include printing methods such as screen printing and gravure printing, and dispensing methods. Drying is performed to remove the solvent, and is usually performed at a temperature of 120° C. or higher for 10 minutes or more. If the solvent remains in the coating layer, there is a risk that the binder component will not be sufficiently removed in the subsequent provisional firing.

[0057] The coating layer is pre-baked to form a pre-baked layer. The pre-baking is performed by heating to a temperature equal to or lower than the glass transition point of the glass composition to remove the binder component, and then heating to a temperature equal to or higher than the softening point of the glass composition contained in the sealing material. The pre-baking temperature is preferably 750 to 850°C, and more preferably 750 to 800°C. Next, the second substrate provided with the pre-fired layer and the first substrate provided with the electronic element section are laminated together, with the pre-fired layer and the electronic element section facing each other. Thereafter, the pre-fired layer is fired to form a sealing layer. The pre-fired layer can be fired, for example, by placing a laminate of the second substrate on which the pre-fired layer is provided and the first substrate on which the electronic element part is provided in a firing furnace such as an electric furnace and heating the entire structure. The firing temperature is preferably 750 to 850°C, more preferably 750 to 800°C. According to the glass composition of this embodiment, a sealing layer with excellent adhesion can be formed even at low pre-firing and firing temperatures of preferably 850° C. or less, more preferably 800° C. or less, and therefore deterioration of the element can be suppressed. In this manner, a sealed package is manufactured in which the electronic element portion is hermetically sealed between the first substrate and the second substrate by the sealing layer.

[0058] <Substrate with coating layer> The substrate with a cover layer to which the glass composition of the present embodiment is applied will be described. 2, a substrate 20 with a cover layer of this embodiment includes a substrate 21 and a cover layer 22 that covers at least one main surface of the substrate 21. The cover layer 22 contains the glass composition of this embodiment. The substrate 21 is, for example, an element substrate mainly provided with an electrode 23. The electrode 23 is provided on one main surface of the substrate 21, and a covering layer 22 is further formed so as to cover the electrode 23.

[0059] The substrate 21 has a thermal expansion coefficient of 60×10 -7 ~90×10 -7 An alumina substrate having a temperature of about 1000° C. / ° C. is preferably used. An alumina substrate is preferred from the viewpoint of particularly good adhesion to a coating layer containing the glass composition of the present embodiment.

[0060] The electrode 23 is made of a metal such as Au.

[0061] A method for producing a substrate with a cover layer according to this embodiment will be described. The glass paste of this embodiment described above is used as the coating material. The glass paste is applied to the object to be coated (electrode 23) of the substrate 21, and then dried to form a coating layer. Coating methods include printing methods such as screen printing and gravure printing, and dispensing methods. Drying is performed to remove the solvent, and is usually performed at a temperature of 120° C. or higher for 10 minutes or more. If the solvent remains in the coating layer, there is a risk that the binder component will not be sufficiently removed in the subsequent provisional firing.

[0062] The coating layer is pre-baked to form a pre-baked layer. The pre-baking is performed by heating to a temperature equal to or lower than the glass transition point of the glass composition to remove the binder component, and then heating to a temperature equal to or higher than the softening point of the glass composition contained in the coating material. The pre-baking temperature is preferably 750 to 850°C, and more preferably 750 to 800°C. Thereafter, the pre-fired layer is fired to form a coating layer. For example, the pre-fired layer may be fired by placing the substrate on which the pre-fired layer is provided in a firing furnace such as an electric furnace and heating the entire substrate. The firing temperature is preferably 750 to 850°C, and more preferably 750 to 800°C. According to the glass composition of this embodiment, a coating layer with excellent adhesion can be formed even at low pre-firing and firing temperatures of preferably 850° C. or less, more preferably 800° C. or less, so that deterioration of the electrodes can be suppressed. In this manner, a substrate with a covering layer is produced.

[0063] Based on the above, this specification discloses the following glass compositions, etc. [1] Substantially free of Pb; In terms of mass% based on oxides, SiO 2 66~75% B 2 O 3 5 to 11.5%, Li 2 0.5 to 10% O Na 2 O 0 to 10%, K 2 O 0 to 10%, BaO 3.1-10%, Al 2 O 3 0 to 4%, A glass composition comprising: [2] Substantially free of Pb; In terms of mass% based on oxides, SiO 2 67-74% B 2 O 3 6 to 11.5%, Li 2 0.5 to 5% O Na 2 O 3-8%, K 2 O 3-8%, BaO 3.2-8%, Al 2 O 3 1.5 to 4%, A glass composition comprising: [3] Substantially free of Pb; In terms of mass% based on oxides, SiO 2 67-72% B2 O 3 8 to 11.5%, Li 2 0.5-2% O Na 2 O 5-8%, K 2 O 3 to 6.5%, BaO 3.3-7%, Al 2 O 3 2 to 4%, A glass composition comprising: [4] BaO, Li 2 O, Na 2 OK 2 O, Al 2 O 3 , and SiO 2 Regarding the content in mass% based on oxides, (4BaO+3Li 2 O+2Na 2 O+K 2 O) / (Al 2 O 3 +SiO 2 ) is 0.41 to 0.70. [5] BaO, Li 2 O, Na 2 OK 2 O, Al 2 O 3 , and SiO 2 Regarding the content in mass% based on oxides, (4BaO+3Li 2 O+2Na 2 O+K 2 O) / (Al 2 O 3 +SiO 2 ) is 0.42 to 0.68. [6] BaO, Li 2 O, Na 2 OK 2 O, Al 2 O 3 , and SiO 2 Regarding the content in mass% based on oxides, (4BaO+3Li2 O+2Na 2 O+K 2 O) / (Al 2 O 3 +SiO 2 ) is 0.45 to 0.64. [7] A glass paste comprising the glass composition according to any one of [1] to [6]. [8] A first substrate and a second substrate facing each other; A sealing package including a sealing layer that bonds the first substrate and the second substrate, The sealing layer comprises the glass composition according to any one of [1] to [6]. [9] a substrate; A substrate with a coating layer comprising a coating layer that covers at least one main surface of the substrate, A substrate with a covering layer, the covering layer comprising the glass composition according to any one of [1] to [6]. EXAMPLES

[0064] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0065] <Production of Glass Composition (Glass Powder)> First, glass raw materials were prepared so as to have the glass composition shown in Table 1, and mixed uniformly. The mixed glass raw materials were then placed in a platinum crucible and melted at 1530°C for 2 hours, after which they were formed into a film. Next, the obtained film-like glass was pulverized in a ball mill, and then a glass powder for sealing and a glass powder for coating were produced under the following conditions. As the glass powder for sealing, a glass composition (glass powder) having an average particle size D50 of 6.0 μm or less and a maximum particle size Dmax of 40 μm or less was obtained for each example. As the glass powder for coating, a glass composition (glass powder) having an average particle size D50 of 2 μm or less and a maximum particle size Dmax of 6 μm or less was obtained for each example. The glass compositions shown in Table 1 are expressed in mass % on an oxide basis.

[0066] <Paste> The glass composition of each example was mixed with a vehicle and kneaded in a three-roll mill to obtain a glass paste. The vehicle used was a composition containing 8% by mass of ethyl cellulose, 72% by mass of 2,2,4-trimethyl-1,3-pentadiol monoisobutyrate, 5% by mass of diethylene glycol monobutyl ether acetate, and 15% by mass of diethylene glycol mono-2-ethylhexyl ether.

[0067] <Measurement of glass transition point (Tg) and softening point (Ts)> For the obtained glass powder of each example, the glass transition point (Tg) and the softening point (Ts) were measured by a macro-type differential thermal analyzer (DTA). The results are shown in Table 1. The softening point (Ts) is the temperature of the fourth inflection point measured by a macro-type differential thermal analyzer (DTA).

[0068] <Evaluation of Adhesion> The obtained sealing glass paste of each example was applied onto one main surface of an alumina substrate by screen printing using a #165 screen, dried at 120°C for 30 minutes, and pre-fired at any temperature between 800 and 850°C for 10 minutes to obtain a pre-fired layer. Two alumina substrates with pre-fired layers were prepared using the method described above. The two substrates were bonded together with the pre-fired layers facing each other, and then fired based on the following criteria to form a sealing layer, and their adhesion was evaluated. A red penetrant was allowed to penetrate between the two alumina substrates, and adhesion was judged to be successful if it was confirmed that there was no color change in the sealing area. A: Manufactured and bonded at a firing temperature of 800°C or higher and less than 825°C B: Manufactured and bonded at a firing temperature of 825°C or higher and less than 850°C C: No adhesion at any firing temperature range

[0069] <Evaluation of surface roughness> The obtained glass paste of each example was applied onto one main surface of an alumina substrate by screen printing using a #400 screen, dried at 120°C for 30 minutes, and fired at any temperature of 800 to 850°C for 10 minutes to obtain a coating layer. The maximum height Ra of the surface of the resulting coating layer was measured using a Surfcom 1400D manufactured by Tokyo Seimitsu Co., Ltd., and the surface roughness was evaluated based on the following criteria. A: Ra is 0.15 μm or less B:Ra is more than 0.15μm and less than 0.3μm C: Ra is over 0.3 μm

[0070] <Measurement of thermal expansion coefficient> The glass powder obtained in each example was pressed and molded, and then fired at 800° C. to obtain a sintered body. The sintered body was processed to a diameter of 5 mm and a length of 20 mm, and the thermal expansion curve (horizontal axis: temperature, vertical axis: sintered body length) at 50 to 350 °C was measured with a thermal expansion meter (RIGAKU Thermoplus2 system TMA8310) at a heating rate of 10 °C / min. The average linear thermal expansion coefficient α (unit: 10 -7 / °C) was calculated. The results are shown in the table.

[0071] <Evaluation of acid resistance> The glass powder obtained in each example was pressed and molded, and then fired at 800° C. to obtain a sintered body. The sintered body was processed to a diameter of 5 mm and a length of 20 mm, and immersed in an aqueous solution of HCl (10%) at room temperature for one week, and the acid resistance was evaluated based on the following criteria. A: Weight loss is less than 0.2% by mass B: Weight loss is 0.2% by mass or more and less than 0.5% by mass

[0072] <Evaluation of alkali resistance> The glass powder obtained in each example was pressed and molded, and then fired at 800° C. to obtain a sintered body. The sintered body was processed to have a diameter of 5 mm and a length of 20 mm, and was immersed in an aqueous solution of NaOH (10%) at room temperature for one week, and the alkali resistance was evaluated based on the following criteria. A: Weight loss is less than 0.2% by mass B: Weight loss is 0.2% by mass or more and less than 0.5% by mass

[0073] <Productivity evaluation> Glasses in which phase separation or non-melting was observed during preparation were rated C (failed). In the table, "phase separation" means phase separation, and "non-melting" means non-melting.

[0074] The evaluation results are shown in Table 1 below. Examples 1 to 13 are working examples, and Examples 14 to 18 are comparative examples.

[0075] [Table 1]

[0076] From the above results, the glass compositions of Examples 1 to 13 were excellent in adhesion as a sealing layer even at a sintering temperature of 850° C. or less, even though they did not substantially contain lead, and the productivity of the glass was also good. -7 ~78×10 -7 / °C, which is close to the thermal expansion coefficient of the alumina substrate. Furthermore, sufficient acid resistance and alkali resistance were also demonstrated. On the other hand, in the glass compositions of Examples 14 to 18, which do not satisfy the glass composition according to the embodiment of the present invention, phase separation and non-melting occurred, making the production of the glass itself difficult. [Industrial Applicability]

[0077] The glass composition according to the embodiment of the present invention satisfies the various properties required for a glass for covering or sealing electrodes or elements, even though it is substantially free of lead. In particular, it has excellent sinterability, acid resistance, and alkali resistance, and is suitable for covering or sealing alumina ceramics in terms of compatibility of thermal expansion coefficient. [Explanation of symbols]

[0078] 10: Sealed package 11: First substrate 12: Second board 13: Electronic device section 15: Sealing layer 20: Substrate with coating layer 21: Substrate 22: Covering layer 23: Electrode

Claims

1. Contains substantially no Pb, In terms of mass% based on oxides, SiO 2 66 to 75 percent, B 2 O 3 5 to 11.5%, Li 2 Oを0.5~10%、 Na 2 Oを0~10%、 K 2 O 0 to 10%, BaO 3.1 to 10%, Al 2 O 3 を0~4%、 A glass composition comprising:

2. Contains substantially no Pb, In terms of mass% based on oxides, SiO 2 67 to 74 percent, B 2 O 3 6 to 11.5%, Li 2 Oを0.5~5%、 Na 2 Oを3~8%、 K 2 O 3-8%, BaO 3.2 to 8%, Al 2 O 3 を1.5~4%、 A glass composition comprising:

3. Contains substantially no Pb, In terms of mass% based on oxides, SiO 2 67-72% B 2 O 3 8 to 11.5%, Li 2 Oを0.5~2%、 Na 2 Oを5~8%、 K 2 O 3 to 6.5%, BaO 3.3 to 7%, Al 2 O 3 を2~4%、 A glass composition comprising:

4. BaO, Li 2 O, Na 2 O.K. 2 O, Al 2 O 3 , and SiO 2 Regarding the content in mass% based on oxides, (4BaO+3Li 2 O + 2Na 2 O+K 2 O) / (Al 2 O 3 +SiO 2 2. The glass composition according to claim 1, wherein the σ is 0.41 to 0.

70.

5. BaO, Li 2 O, Na 2 O.K. 2 O, Al 2 O 3 , and SiO 2 Regarding the content in mass% based on oxides, (4BaO+3Li 2 O + 2Na 2 O+K 2 O) / (Al 2 O 3 +SiO 2 2. The glass composition according to claim 1, wherein σ is 0.42 to 0.

68.

6. BaO, Li 2 O, Na 2 O.K. 2 O, Al 2 O 3 , and SiO 2 Regarding the content in mass% based on oxides, (4BaO+3Li 2 O + 2Na 2 O+K 2 O) / (Al 2 O 3 +SiO 2 2. The glass composition according to claim 1, wherein σ is 0.45 to 0.

64.

7. A glass paste comprising the glass composition according to any one of claims 1 to 6.

8. an opposing first substrate and a second substrate; A sealing package including a sealing layer that bonds the first substrate and the second substrate, A sealed package, wherein the sealing layer comprises the glass composition according to any one of claims 1 to 6.

9. A substrate; A substrate with a coating layer comprising a coating layer that covers at least one main surface of the substrate, A substrate with a coating layer, wherein the coating layer comprises the glass composition according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • sealing glass suspension

    JP2000505414A